Leveled Texts for Classic Fiction : Shakespeare. - Hollingsworth, Tamara (Leveled Texts., 2013)
Differentiate instruction with excerpts from 15 different Shakespeare plays written at four different reading levels. Each text focuses on setting, character, plot, or language usage and can be used for close reading or small-group instruction.